MATHEMATICAL MODELS IN ECONOMICS - A.I.Sotvoldiev; D.I.Ostonakulov (Journals Park Publishing, 2023)
Mathematics is inextricably linked with other sciences. It is an apparatus with which you can explore, analyze and solve problems. We can build mathematical models when solving various problems of physics, chemistry, economics, etc. The purpose of my work was to consider examples of economic problems using a mathematical apparatus. The main tasks were the construction of mathematical models of various types of problems. In the course of my work, I would like to see the application of mathematics in the science of economics. In the tasks I tried to rely on various mathematical functions. The work consists of two parts. The first part deals with theoretical questions about mathematical models in economics. In the second part I show examples – different types of tasks.
Keywords: mathematical modeling, economics, model, linear dependence.